Geometric Morphometrics Approach on Genotoxicity Evaluation of Ecdysone Agonist, Chromafenozide on Corcyra Cephalonica Stainton (Lepidoptera: Pyralidae) - E.M, Manogem; P.K, Soumya; Y, Shibu (International Journal of Engineering and Technology, 2018)
The present investigation attempted to evaluate the genotoxicity effect of ecdysone agonist, on the wing architecture using the land mark based shape analysis through geometric morphometrics. The study revealed that the fore and hind wings of treated male and female showed significant variation in shape. High significance in shape was observed in male fore and hind wings. But, variation in size was not affected. The analysis of symmetry and asymmetry between left and right wings, suggests that the untreated male exhibit shape difference between left and right forewings and similar variation was also found in forewings of treated female. These findings demonstrate that, chromafenozide treated on the egg masses produced genotoxic effect on the adult wing architecture of C. cephalonica. Both the male and female forewing showed high significant shape decomposition at P = 0.0001 level exposed to 1/5 EC50 of chromafenozide. The morphological alteration in wing shape suggests that, it affects the aerodynamics pattern of the insect. In the present study, species diagnosis was performed in laboratory reared F1 generation using multilocus barcoding technique and obtained a sequence of 658bp (CO I) and 563bp (18s) in length.Â Â